Death Due to Intra-aortic Migration of Kirschner Wire From the Clavicle: A Case Report and Review of the Literature. Issue 21 (May 2016) - Tan, Lei; Sun, Da-Hui; Yu, Tiecheng; Wang, Linxiang; Zhu, Dong; Li, Yan-Hui
Abstract : Abstract: Migration of orthopedic fixation wires into the ascending aorta though a rare occurrence can have devastating consequences. Therefore, prompt recognition, with immediate and cautious retrieval of the implant is paramount in averting these complications. We present a case of a 5-year-old boy with the intra-aortic migration of a K-wire used for the treatment of a right clavicle fracture. He was transferred to us with a history of syncope, chest pain, and shortness of breath 7 days after K-wire placement, which was performed at another hospital. On CT scan, the wire was found to be partially inside the ascending aorta, which was associated with massive hemopericardium and cardiac tamponade. The patient was taken up for emergency surgery for the removal K-wire and for the management of cardiac temponade. However, the patient developed cardiac arrest during the induction of intravenous anesthesia and endotracheal intubation. The K-wire was retrieved from the thorax via thoracotomy. However, the patient died 10 days after the surgery. As the migration of wires and pins during orthopedic surgery can cause potentially fatal complications, these should be used very cautiously, especially for percutaneous treatment of shoulder girdle fractures. The patients with such implants should be followed frequently, both clinically and radiographically. If migration occurs, the patient should be closely monitored for emergent complications and the K-wire should be extracted immediately.